2010
DOI: 10.1007/s00405-010-1378-9
|View full text |Cite
|
Sign up to set email alerts
|

Rule 3,000: a more reliable precursor to perceive vestibular schwannoma on MRI in screened asymmetric sensorineural hearing loss

Abstract: Nine different definitions of asymmetric sensorineural hearing loss (SNHL) have been reported in literature. The objectives of this study are to: (1) compare all these definitions of asymmetric SNHL; (2) measure the agreement between these definitions in detecting vestibular schwannoma (VS); and (3) determine the strongest association between an asymmetric SNHL definition and positive VS on magnetic resonance imaging (MRI). The study is a retrospective chart review in a tertiary care center. Cases were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 14 publications
1
35
1
Order By: Relevance
“…Moreover, the mean audiogram pattern exhibited by both groups involved a loss of high tone, with no significant difference observed between the 2 groups. Recently, an asymmetric SNHL of 15 dB or more at a frequency 3,000 Hz (e.g., the rule 3,000) has been described as a universal referral guide for further MRI investigations (19). In the current study, highly significant differences ( p G 0.001) were found between affected and nonaffected ears at all frequencies for both groups.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the mean audiogram pattern exhibited by both groups involved a loss of high tone, with no significant difference observed between the 2 groups. Recently, an asymmetric SNHL of 15 dB or more at a frequency 3,000 Hz (e.g., the rule 3,000) has been described as a universal referral guide for further MRI investigations (19). In the current study, highly significant differences ( p G 0.001) were found between affected and nonaffected ears at all frequencies for both groups.…”
Section: Discussionmentioning
confidence: 65%
“…A consensus is emerging that, for most of the cases, magnetic resonance is the imaging modality of choice for lesions of the cerebellopontine angle and internal auditory canal (Zamani, 2000;Adunka et al, 2007;Saliba et al, 2010;Sriskandan and Connor, 2011;Yoshida et al, 2011). However, when visualization of the internal auditory canal and/or of the bony cochlear nerve canal is needed, then high-resolution CT is best as it allows better evaluation of bony structures (Adunka et al, 2007).…”
Section: Neuroimagingmentioning
confidence: 97%
“…In a second retrospective chart review, Saliba et al compared the diagnostic efficiency of eight published definitions of asymmetry in their series of audiograms among patients referred to their tertiary center with VS versus a separate control group. Among 84 patients with VS they found that the rule 3000 ( ≥ 5 dB at 3 kHz) had the greatest diagnostic accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among 84 patients with VS they found that the rule 3000 ( ≥ 5 dB at 3 kHz) had the greatest diagnostic accuracy. Saliba estimated that their method would detect VS in about 2% of MRI scans …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation